2015
DOI: 10.1128/mcb.01439-14
|View full text |Cite
|
Sign up to set email alerts
|

Otoferlin Deficiency in Zebrafish Results in Defects in Balance and Hearing: Rescue of the Balance and Hearing Phenotype with Full-Length and Truncated Forms of Mouse Otoferlin

Abstract: Sensory hair cells convert mechanical motion into chemical signals.Otoferlin, a six-C2 domain transmembrane protein linked to deafness in humans, is hypothesized to play a role in exocytosis at hair cell ribbon synapses. To date, however, otoferlin has been studied almost exclusively in mouse models, and no rescue experiments have been reported. Here we describe the phenotype associated with morpholino-induced otoferlin knockdown in zebrafish and report the results of rescue experiments conducted with full-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 56 publications
6
72
0
Order By: Relevance
“…Figure 11 shows the expression of over 80 genes that have been implicated in human deafness or related to hearing in animal models. col11a1a, col11ab, col11a2, col4a5, dfna5b, eya1, eya2, grhl2a, grhl2b, kcnq4, otofa, otofb, and slc26a5 are highly expressed in the zebrafish otic vesicle, hair cells, and semicircular canal (Croushore , 2005;Blasiole et al, 2006;Albert et al, 2007;Xiao and Baier, 2007;Baas et al, 2009;Yokoi et al, 2009;Fang et al, 2010;Hoffman et al, 2010;Janicke et al, 2010;Landgraf et al, 2010;Wu et al, 2014;Chatterjee et al, 2015;Wang et al, 2015). col11a1 has been shown to express in the inner ear and otic capsule of mice (Yoshioka et al, 1995;Diez-Roux et al, 2011) and spontaneous mutation mouse models show both auditory and vestibular abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 11 shows the expression of over 80 genes that have been implicated in human deafness or related to hearing in animal models. col11a1a, col11ab, col11a2, col4a5, dfna5b, eya1, eya2, grhl2a, grhl2b, kcnq4, otofa, otofb, and slc26a5 are highly expressed in the zebrafish otic vesicle, hair cells, and semicircular canal (Croushore , 2005;Blasiole et al, 2006;Albert et al, 2007;Xiao and Baier, 2007;Baas et al, 2009;Yokoi et al, 2009;Fang et al, 2010;Hoffman et al, 2010;Janicke et al, 2010;Landgraf et al, 2010;Wu et al, 2014;Chatterjee et al, 2015;Wang et al, 2015). col11a1 has been shown to express in the inner ear and otic capsule of mice (Yoshioka et al, 1995;Diez-Roux et al, 2011) and spontaneous mutation mouse models show both auditory and vestibular abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…Our observation that multiple C2 domains interact with Cav1.3 suggests that some C2 domains may be somewhat functionally redundant. Indeed, it was reported that exogenous truncated forms of otoferlin lacking one or more C2 domains could rescue balance and startle reflex in zebrafish lacking endogenous otoferlin (25). This observation may be explained if the truncated otoferlin constructs retained at least one C2 domain capable of binding Cav1.…”
Section: Discussionmentioning
confidence: 99%
“…Otoferlin has been detected in hair cells of multiple species including zebrafish (Goodyear et al, 2010). A recent study using morpholinos against otoferlin a and otoferlin b showed that double knockdown resulted in defective balance and hearing in zebrafish larvae (Chatterjee et al, 2015). Rescue experiments using various deletions of the C2 domains revealed that the C-terminal C2 domains are critical for function (Chatterjee et al, 2015).…”
Section: Functional Aspects Of Ribbon Synapsesmentioning
confidence: 99%
“…A recent study using morpholinos against otoferlin a and otoferlin b showed that double knockdown resulted in defective balance and hearing in zebrafish larvae (Chatterjee et al, 2015). Rescue experiments using various deletions of the C2 domains revealed that the C-terminal C2 domains are critical for function (Chatterjee et al, 2015). Aside from a severe reduction of exocytosis in hair cells, which is presumably the case in the zebrafish knockdowns, the deletion of otoferlin in mice results in a significant decrease in the number of ribbons (Roux et al, 2006).…”
Section: Functional Aspects Of Ribbon Synapsesmentioning
confidence: 99%